The Mona Lisa effect: Neural correlates of centered and off‐centered gaze. Issue 2 (18th October 2014) - Boyarskaya, Evgenia; Sebastian, Alexandra; Bauermann, Thomas; Hecht, Heiko; Tüscher, Oliver
Abstract The Mona Lisa effect describes the phenomenon when the eyes of a portrait appear to look at the observer regardless of the observer's position. Recently, the metaphor of a cone of gaze has been proposed to describe the range of gaze directions within which a person feels looked at. The width of the gaze cone is about five degrees of visual angle to either side of a given gaze direction. We used functional magnetic resonance imaging to investigate how the brain regions involved in gaze direction discrimination would differ between centered and decentered presentation positions of a portrait exhibiting eye contact. Subjects observed a given portrait's eyes. By presenting portraits with varying gaze directions—eye contact (0°), gaze at the edge of the gaze cone (5°), and clearly averted gaze (10°), we revealed that brain response to gaze at the edge of the gaze cone was similar to that produced by eye contact and different from that produced by averted gaze. Right fusiform gyrus and right superior temporal sulcus showed stronger activation when the gaze was averted as compared to eye contact. Gaze sensitive areas, however, were not affected by the portrait's presentation location. In sum, although the brain clearly distinguishes averted from centered gaze, a substantial change of vantage point does not alter neural activity, thus providing a possible explanation why the feeling of eye contact is upheld even in decentered stimulus positions. Hum Brain Mapp 36:619–632, 2015. © 2014 Wiley Periodicals, Inc.